2011
DOI: 10.1007/s12262-011-0331-5
|View full text |Cite
|
Sign up to set email alerts
|

Prevention and Management of Complications of Laparoscopic Splenectomy

Abstract: Laparoscopic splenectomy (LS) has become a commonly performed minimal-access operation. With increasing experience, surgeons are undertaking LS for multiple pathologies and tackling spleens of diverse sizes. LS remains a challenging procedure to be performed by experienced laparoscopic surgeons, well supported by a team. Bleeding remains the commonest intraoperative complication and perhaps the commonest reason for conversion to a laparotomy. Although the incidence of postoperative complications following LS i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
0
19
0
6
Order By: Relevance
“… 3 , 4 , 15 , 21 Therefore, co-infected ( S. mansoni infection and HBV or HCV) patients are at higher risk for early deterioration of liver function, the development of cirrhosis, and rapid progression towards end-stage liver disease and even HCC. 20 , 21 , 23 In our sample, there were four (57.1%) patients with immunity by contact for HBV. The possible influence of this result on the disease course of these patients is unknown.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“… 3 , 4 , 15 , 21 Therefore, co-infected ( S. mansoni infection and HBV or HCV) patients are at higher risk for early deterioration of liver function, the development of cirrhosis, and rapid progression towards end-stage liver disease and even HCC. 20 , 21 , 23 In our sample, there were four (57.1%) patients with immunity by contact for HBV. The possible influence of this result on the disease course of these patients is unknown.…”
Section: Discussionmentioning
confidence: 73%
“…In studies where routine postoperative ultrasonography was done after splenectomy, the incidence of TPV ranged from 6.3 to 10.0%. 20 …”
Section: Discussionmentioning
confidence: 99%
“…[ 6 ] Our patient had the splenic weight of 3270 g. Unfortunately, the weight of the spleen cannot be accurately determined before surgery, but the presence of massive splenomegaly must lead to a presumption of increased risk of PVT. Thrombosis of the splenoportal axis is being increasingly recognised even after laparoscopic splenectomy,[ 7 ] being reported as high as 55% in one study. [ 8 ] This high probability of SPVT should make us reconsider the use of epidural anaesthesia and analgesia in such cases.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] However, total splenectomy may lead to overwhelming post-splenectomy infection (OPSI), portal vein thrombosis, and other complications. [ 3 , 4 ] A previous study suggested that total splenectomy may also increase the risks of pulmonary hypertension, atherosclerosis, and coronary heart disease. [ 5 ] As understanding of splenic function increases, especially immunologic function, a growing number of surgeons are implementing spleen-preserving surgery.…”
Section: Introductionmentioning
confidence: 99%